1982
DOI: 10.1111/j.2042-3306.1982.tb02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Equine abortion associated with Enterobacter agglomerans

Abstract: Summary During a 20 month period Enterobacter agglomerans was isolated from 17 cases of equine abortion. In 8 cases E agglomerans was isolated in pure culture and in 9 cases it was isolated in mixed culture from the foetus and/or foetal membranes. Fifteen cases had histological evidence of foetal infection and/or placentitis. The occurrence of E agglomerans in pure culture, associated with inflammatory lesions in the foetus and foetal membranes, suggests it to be a cause of abortion in mares. Résumé Durant une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The bacteria isolated from the placenta were comparable to those isolated from the outer genital tract. 6,5 The lesional distribution also supported this ascending infection hypothesis, especially lesions caused by fungi and those of chronic placentitis, which frequently affected the cervical star area. 9 However, some bacteria were able to reach the placenta via the blood stream, especially those cases in which abortion occurred at earlier gestational age and bacterial emboli were ob-served in the placenta and fetal tissues.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The bacteria isolated from the placenta were comparable to those isolated from the outer genital tract. 6,5 The lesional distribution also supported this ascending infection hypothesis, especially lesions caused by fungi and those of chronic placentitis, which frequently affected the cervical star area. 9 However, some bacteria were able to reach the placenta via the blood stream, especially those cases in which abortion occurred at earlier gestational age and bacterial emboli were ob-served in the placenta and fetal tissues.…”
Section: Discussionsupporting
confidence: 55%
“…13,14 The most commonly reported pathogens associated with equine placentitis cases in previous studies have been S. zooepidemicus, fungi, E. coli, P. aeruginosa, Enterobacter sp., and K. pneumoniae. 5,14,16,[18][19][20] The frequency of bacteria or fungi isolated or demonstrated from the placenta varies with geographic area and changes with time. Whitewell 20 reported a high incidence of mycotic placentitis in a 10-year study in England.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to humans, there are only few reports on infections caused by Pantoea agglomerans in vertebrate animals. Gibson et al [60] has identified P. agglomerans as a possible cause of equine abortion on the basis of positive cultures from aborted foetuses and/or foetal membranes associated with the presence of inflammatory lesions, mostly appearing as interstitial pneumonia, which had been evidenced by histopathological examination. Considering the known affinity of P. agglomerans to mammalian macrophages [55], the electron micrograph reproduced by authors is very meaningful, showing numerous bacteria engulfed within a cytoplasmic vacuole of an alveolar macrophage of aborted foetus (Fig.…”
Section: Causative Agent Of Infections In Animalsmentioning
confidence: 99%
“…According to the reports on the epizootic situation with animal infection diseases in the Russian Federation (https://fsvps.gov.ru/fsvps/iac/rf/reports.html), cases of bacterial infectious diseases associated with reproductive system pathologies are annually registered on the territory of the Russian Federation. In addition to pathogenic microbes, opportunistic microorganisms, including the representatives of the Enterobacteriaceae family and etc., can play an important role as causative agents of infectious diseases in animals [1,2]. The emergence and spread of antibiotic-resistant variants of these types of microorganisms is of serious concern to world health and veterinary specialists.…”
Section: Introductionmentioning
confidence: 99%